PENGARUH PEMBELAJARAN DARING, PENGUASAAN IT, DAN TANGGUNG JAWAB GURU TERHADAP PRESTASI BELAJAR SISW DI MI SE-KECAMATAN LEMPUING SUMATERA SELATAN - Nikmatul Khoiriyah; Adi Wijayanto; Prim Masrokan Mutohar (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
The objective of this study is to find out the effect of online learning, mastery of IT, and teacher responsibility on student achievement in MI of Lempuing Subdistrict, South Sumatra. Information and communication technology in the current pandemic conditions has a major influence on the world of education, especially in planning, process, and evaluation activitiesThis type of research was correlation research with 100 samples. This study used multiple regression analysis to determine whether there is a significant effect between the variables X on Y.After the data were collected, then hypothesis testing was carried out using SPSS 22.0 For Windows and obtained the following results: (1) Results Based on the analysis obtained Fcount = 4.070 and Fable = 3.94 at a significance level of 5% because Fcount > Ftable means that there was a significant effect of learning on student achievement. (2) Based on the results of the analysis obtained Fcount = 4,400 and Fable = 3, 94 at the 5% significance level because Fcount > Ftable means that there was a significant influence on IT mastery on student achievement. (3) Based on the analysis obtained Fcount = 4.211 and Fable = 3.94 at a significance level of 5% because Fcount > Ftable means that there was a significant effect of teacher responsibility on learning achievement. (4) Based on the analysis shown by the ANOVA output with Fount > Ftable (4,844 > 3,94) and the coefficient of output level 0,004 < 0,05. It could be concluded that Ho was rejected and he was accepted so there was a significant influence on IT mastery, teacher responsibility, and learning courage on student achievement in MI of Lempuing Subdistrict, South Sumatra.